Identification and Clinical Characteristics of Community-Acquired Acinetobacter baumannii in Patients Hospitalized for Moderate or Severe COVID-19 in Peru - Silva-Caso, Wilmer (2024)
Acinetobacter baumannii has been described as a cause of serious community-acquired infections in tropical countries. Currently, its implications when simultaneously identified with other pathogens are not yet adequately understood. A descriptive study was conducted on hospitalized patients with a diagnosis of moderate/severe SARS-CoV-2-induced pneumonia confirmed via real-time RT-PCR. Patients aged > 18 years who were admitted to a specialized COVID-19 treatment center in Peru were selected for enrollment. A. baumannii was detected via the PCR amplification of the blaOXA-51 gene obtained from nasopharyngeal swabs within 48 h of hospitalization. A total of 295 patients with COVID-19 who met the study inclusion criteria were enrolled. A. baumannii was simultaneously identified in 40/295 (13.5%) of COVID-19-hospitalized patients. Demographic data and comorbidities were comparable in both Acinetobacter-positive and -negative subgroups. However, patients identified as being infected with Acinetobacter were more likely to have received outpatient antibiotics prior to hospitalization, had a higher requirement for high-flow nasal cannula and a higher subjective incidence of fatigue, and were more likely to develop Acinetobacter-induced pneumonia during hospitalization. Conclusions: The group in which SARS-CoV-2 and A. baumannii were simultaneously identified had a higher proportion of fatigue, a higher frequency of requiring a high-flow cannula, and a higher proportion of superinfection with the same microorganism during hospitalization.